Aku adalah Perempuan Pesantren: Sebuah Etnografi Biografi - Iklilah Muzayyanah (Antropologi Indonesia, 2011)
This paper is based on the reflections of the life experiences of a woman that grew up within the cultures of the Pesantren. At first, this paper was merely for academic purposes that demanded reflective research. Most of the data was collected in a reasonably short amount of time in the last two months of 2010 by relying on life experience memories and enforced by data from results of observations, interviews and personal documents. This research tries to give an overview and becomes a small part of an effort to understanding how a human woman brought up within the cultures of the Pesantren interprets herself as a woman. A woman who deals with various feelings, thoughts, questions, concerns and expectations in between habits and habituations embedded in the existing culture. Although admittedly, this paper does not intend to give a generalization of the Pesantren culture, especially on the ways of how one “grows into a woman” and the social consequences of the female self. Keywords: pesantren, ning, woman, culture